Catalytic Degradation of Benzene over Nanocatalysts containing Cerium and Manganese. Issue 5 (21st September 2016) - Wang, Zhen; Deng, Yuzhou; Shen, Genli; Akram, Sadia; Han, Ning; Chen, Yunfa; Wang, Qi
Abstract: A Ce–Mn composite oxide possessing a rod‐like morphology (with a fixed molar ratio of Ce/Mn=3:7) was synthesized through a hydrothermal method. Mn ions were doped into a CeO2 framework to replace Ce ions, thereby increasing the concentration of oxygen vacancies. The formation energies of O vacancies for the Ce–Mn composite oxide were calculated by applying density functional theory (DFT). The data showed that it was easier to form an O vacancy in the composite. The catalytic behavior of the Ce–Mn composite oxide for benzene degradation was researched in detail, which exhibited a higher activity than the pure phases. Based on this, the Ce–Mn composite oxide was chosen as a supporter to load PdO nanoparticles. The activity was enhanced further compared with that of the supporter alone (for the supporter, the reaction rate R 214 °C =0.68×10 −4 mol gcat −1 s −1 and apparent activation energy E a =12.75 kJ mol −1 ; for the supporting catalyst, R 214 °C =1.46×10 −4 mol gcat −1 s −1, E a =10.91 kJ mol −1 ). The corresponding catalytic mechanism was studied through in situ Raman and FTIR spectroscopy, which indicated that the process of benzene oxidation was related to different types of oxygen species existing at the surface of the catalysts. Abstract : Various vacancies : The catalytic oxidation of benzene goes through several stages. In general, a benzene molecule adsorbed at the surface of a catalyst reacts with surface active oxygen species to obtain the final products (CO2 and H2 O). During the process, surface active oxygen species are closely related to the catalyst microstructure, mainly as oxygen vacancies. Gaseous oxygen is activated at the surface to produce O2 − and O −, which adsorb the surface vacancy; meanwhile, the supporter can release lattice oxygen to form a vacancy (surface and bulk), which can store and transport active oxygen species to ensure the reaction.